Development Massive Open Online Courses (MOOCs) Based on Moodle in High School Physics Static Electricity - Vandan Wiliyanti; Aliya Destiana; Nur Haq Shidqha (Jurnal Pembelajaran Fisika, 2022)
This paper discusses the development of e-learning media in the form of MOOCs (Massive Open Online Course) available on the Moodle website. This research was conducted to determine whether the development of interactive multimedia in the form of Moodle-based MOOCs is appropriate for use in teaching and learning activities of static electricity in high school. The method used in this study is the Research and Development (RD) research method using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The data collection technique used in this study was a questionnaire on the feasibility of learning media. The questionnaire instrument was given to media experts and material experts. The data analysis technique used in this research is descriptive quantitative and qualitative descriptive data analysis techniques. The aspects discussed are the development of learning media in the form of MOOCs, the level of media feasibility and the level of feasibility of the material presented. The results of this study indicate that e-learning media in the form of Moodle-based MOOCs are suitable for use in learning and are able to increase teacher creativity and can be used for distance learning and can train students to learn independently.Keywords: Interactive multimedia, MOOCs, e-Learning, Moodle, Learning physicsDOI: http://dx.doi.org/10.23960/jpf.v10.n1.202206